Optimization of the Thousand Stairs Destination in Cibiru Wetan Village Cileunyi District, Bandung Regency - Retno Dwimarwati; Nanan Supriyatna; Yani Maemunah (Pascasarjana ISBI Bandung Conference Series, 2025)
The Tourism Destination program in Bandung Regency aims to develop fifty tourist villages by 2023. Villages are vital for cultural resilience, as they can preserve and develop culture. Cibiru Wetan Village, selected by the Tourism Village Association (ASIDEWI), has chosen Tangga Seribu as its primary destination. After social mapping, efforts to optimize Tangga Seribu include infrastructure improvements, aesthetic enhancements, and the addition of traditional games. The destination must meet the five A's: accessibility, accommodation, attractions, activities, and amenity. Ethnomethodology is used to understand the community’s mindset, behavior, and perception of tourism, while the participatory method engages the community directly in village development. This program empowers the local community and strengthens tourism as a key economic driver, aligning with local government goals. Keywords: Tourism destination; Optimisation; Potential; Tangga Seribu; Participatory